Appreciation of Catur Sembah in The Context of The Eucharist and Javanese Tradition for Javanese Transmigrants in Tugumulyo Oki, South Sumatera - Iknasius Bayu Lesmana; Atanasius Deimen Wahana Utama; Olaf Shyantica Wisanggeni; Alfonsus Rodriquez Dhandi Pratama (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2024)
Worship is a respectful statement made by humans to establish a relationship with God, with all spiritual and physical aspects. In reality, the practice of worshiping the supreme reality is only practiced as a habit without meaning. This study aims to explore the relationship between the appreciation of worship in the Eucharistic celebration and Javanese cultural practices, as well as to explore the positive impact of the practice of worship in daily life. This research uses the Interpretative Phenomenological Analysis (IPA) method with reference to the concept of Catur Sembah in the Serat Wedhatama. IPA research explored four Catholic transmigrants in Tugumulyo OKI, South Sumatera. The results showed that the four respondents who lived the sembah were able to have a tolerant attitude, keep other people's feelings and be more tolerant.